RESULTS OF APPLYING POLYVITAMIN COMPLEX FOR CHILDREN WITH ATOPIC DERMATITIS - N.A. Ivanova ("Paediatrician" Publishers LLC, 2007)
The article presents findings of applying vitamin-and-mineral complex (VMC) for children frequently suffering from diseases and children with atopic dermatitis. It shows that usage of VMC within a complex therapy promotes regression of subnormal vitamin provision symptoms, as well as symptoms of the core disease. This happens against heightened vitamin content in child's organism - which was proven with the test of A and E vitamins content in blood. The research has demonstrated a quite good tolerance of VMC by children suffering from atopic dermatitis. Key words: children frequently suffering from diseases, atopic dermatitis, vitamins, treatment.